2012
DOI: 10.1590/s1806-00132012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da terapia de suporte nas alterações otológicas em pacientes com desordem temporomandibular

Abstract: BACKGROUND AND OBJECTIVES: Otological symptoms complaints may be associated to temporomandibular joint disorders (TMD). Occlusal splint is an alternative to treat TMD because it provides ideal occlusion to patients, acting on painful symptoms. Considering the conservative and reversible characteristics of supportive therapy with occlusal splints, this study aimed at evaluating its impact on the frequency of otological changes in TMD patients. METHOD: An intervention study was carried out with 35 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…For tinnitus and ear pain, a significant correlation was found when it was related to the beginning or a worsening of otological symptoms were concomitant with the onset or worsening of TMD, even when they were stress-related. Uemoto et al and Nichthauser et al found that the use of muscle-relaxant plates or flat and smooth occlusal appliances were effective in promoting the remission of TMD signs and symptoms and otological symptoms reported together with TMD 9,28 . Another type of therapy adopted was orofacial myofunctional therapy (OMT) applied by Felício et al where it was found that the group of TMD patients who received treatment with OMT presented decreased sensitivity upon palpation and articulation, as well as a decrease in TMD and otological symptoms, proving that this therapy acted positively on the orofacial and otological symptoms presented by patients 10 .…”
Section: Resultsmentioning
confidence: 99%
“…For tinnitus and ear pain, a significant correlation was found when it was related to the beginning or a worsening of otological symptoms were concomitant with the onset or worsening of TMD, even when they were stress-related. Uemoto et al and Nichthauser et al found that the use of muscle-relaxant plates or flat and smooth occlusal appliances were effective in promoting the remission of TMD signs and symptoms and otological symptoms reported together with TMD 9,28 . Another type of therapy adopted was orofacial myofunctional therapy (OMT) applied by Felício et al where it was found that the group of TMD patients who received treatment with OMT presented decreased sensitivity upon palpation and articulation, as well as a decrease in TMD and otological symptoms, proving that this therapy acted positively on the orofacial and otological symptoms presented by patients 10 .…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with findings described in previous studies, in which the larger portion of the sample was composed of women. 6,7,12,20,[22][23][24][25][26][27] To explain…”
Section: Discussionmentioning
confidence: 99%
“…Para manutenção das restaurações e do equilíbrio oclusal alcançado, devido ao histórico do paciente, optou-se pela confecção de placa miorrelaxante, artifício mais difundido de terapêutica dos sintomas das DTMs 28,29 . A placa miorrelaxante é uma terapia indicada por ser conservadora e reversível, que promove relações oclusais e estruturais favoráveis da ATM com a musculatura mastigatória, além de melhorar a função articular 30,31 .…”
Section: Relato De Casounclassified